Foster the application of ISO standards on climate change adaptation in cities - Lindner, Rene; Hernantes, Josune; Jaca, Carmen (Journal of Standardisation, 2024)
A set of ISO standards on climate change adaptation exist that are relevant for the application by cities. However, the knowledge of these is limited among the target groups as well as support is needed to foster their application at city level. The CitISOsCA research project addressed these aspects by different engagement activities using mainly surveys and workshops. The main outcomes of this research are seven verified elements to support applying a standard at city level, and aspects to consider when start the application of a CCA standard in a city. The research fills the gap in literature, which lacks on information on how the application of standards can be fostered.